2020
DOI: 10.9734/jenrr/2020/v4i430133
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Voltage, Current and Power Produced in a Piezoelectric System from Human Foot Beats

Abstract: Aims: This study analysed and compared the amount of voltage, current and power generated in a piezoelectric system from human foot beats. Study Design: The study was an experimental study which made use of piezoelectric materials together with human loads (weights) from the foot beats of dancers in a dance club, and connected to a rechargeable battery and multimeter. In this system, mechanical deformation was expected to cause conversion of mechanical energy to electrical energy which can be stored in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…It might be due to the larger pitch and bevel angle of the Blade-B3 cutter bar [55][56][57][58][59] . Wang et al 54 also reported that with an increase in the pitch of the blade, the cutting force increased 37,38,[60][61][62][63][64][65][66][67][68][69][70][71] . The power requirement was increased with the increase in cutter bar speed.…”
Section: Discussionmentioning
confidence: 98%
“…It might be due to the larger pitch and bevel angle of the Blade-B3 cutter bar [55][56][57][58][59] . Wang et al 54 also reported that with an increase in the pitch of the blade, the cutting force increased 37,38,[60][61][62][63][64][65][66][67][68][69][70][71] . The power requirement was increased with the increase in cutter bar speed.…”
Section: Discussionmentioning
confidence: 98%